Firm productivity and investment climate in developing countries: how does Middle East and North Africa manufacturing perform? - (:unkn) unknown (My University, 2011)
Firm productive performances in five Middle East and North African (MENA) economies and eight manufacturing industries are compared to those in 17 other developing countries. Although the broad picture hides some heterogeneity, enterprises in MENA often performed inadequately given the middle-income status of the MENAeconomies, with the exception of Morocco and, to some extent, Saudi Arabia. Firm competitiveness is a more constant constraint, with a unit labor cost higher than in most competitor countries, as well as investment climate (IC) deficiencies. The empirical analysis also points out how IC matters for firm productivity through the quality of infrastructure, the experience and education of the labor force, the cost and access to financing, and different dimensions of the government-business relationship. These findings bear important policy implications by showing which dimensions of the IC, in which industry, could help manufacturing in MENA to be more competitive in the globalization context.
Keywords: African Research